Integration of Genetic and Process Engineering for Optimized Rhamnolipid Production Using Pseudomonas putida - Tiso, Till; Ihling, Nina; Kubicki, Sonja; Biselli, Andreas; Schonhoff, Andreas; Bator, Isabel; Thies, Stephan; Karmainski, Tobias; Kruth, Sebastian; Willenbrink, Anna-Lena; Loeschcke, Anita; Zapp, Petra; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Rhamnolipids are biosurfactants produced by microorganisms with the potential to replace synthetic compounds with petrochemical origin. To promote industrial use of rhamnolipids, recombinant rhamnolipid production from sugars needs to be intensified. Since this remains challenging, the aim of the presented research is to utilize a multidisciplinary approach to take a step toward developing a sustainable rhamnolipid production process. Here, we developed expression cassettes for stable integration of the rhamnolipid biosynthesis genes into the genome outperformed plasmid-based expression systems. Furthermore, the genetic stability of the production strain was improved by using an inducible promoter. To enhance rhamnolipid synthesis, energy- and/or carbon-consuming traits were removed: mutants negative for the synthesis of the flagellar machinery or the storage polymer PHA showed increased production by 50%. Variation of time of induction resulted in an 18% increase in titers. A scale-up from shake flasks was carried out using a 1-L bioreactor. By recycling of the foam, biomass loss could be minimized and a rhamnolipid titer of up to 1.5 g/L was achieved without using mechanical foam destroyers or antifoaming agents. Subsequent liquid–liquid extraction was optimized by using a suitable minimal medium during fermentation to reduce undesired interphase formation. A technical-scale production process was designed and evaluated by a life-cycle assessment (LCA). Different process chains and their specific environmental impact were examined. It was found that next to biomass supply, the fermentation had the biggest environmental impact. The present work underlines the need for multidisciplinary approaches to address the challenges associated with achieving sustainable production of microbial secondary metabolites. The results are discussed in the context of the challenges of microbial biosurfactant production using hydrophilic substrates on an industrial scale.